PERAN GURU FIQIH DALAM PEMBENTUKAN AKHLAK PESERTA DIDIK - At Tarmizi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
Education is an essential process in developing the quality of human beings, not only in terms of intellectual aspects but also in moral and spiritual dimensions. In this context, the formation of students’ character becomes the primary focus of education, particularly within educational systems grounded in humanistic and religious values. Teachers, as central figures in the educational process, play a crucial role in shaping students’ moral character. This study aims to examine in detail the role of teachers in the development of students’ morality (akhlak), including their roles as educators, mentors, motivators, role models, and facilitators in the learning process. The method employed in this study is a literature review with a qualitative approach, involving the analysis of various sources such as books, academic journals, and relevant Islamic literature. The findings indicate that the development of students’ moral character cannot be separated from the active role of teachers in providing exemplary behavior, habituation, and reinforcement of moral values in daily activities. Teachers are not only responsible for delivering instructional content but also serve as real-life role models in their attitudes, behaviors, and interactions. Teacher exemplification has been proven to be the most significant factor in shaping students’ moral character, as students tend to imitate behaviors they directly observe.